Digital orthodontic radiographic set versus cone-beam computed tomography: an evaluation of the effective dose - Lillian Atsumi Simabuguro Chinem; Beatriz de Souza Vilella; Cláudia Lúcia de Pinho Maurício; Lucia Viviana Canevaro; Luiz Fernando Deluiz; Oswaldo de Vasconcellos Vilella
ABSTRACT Objective: The aim of this study was to compare the equivalent and effective doses of different digital radiographic methods (panoramic, lateral cephalometric and periapical) with cone-beam computed tomography (CBCT). Methods: Precalibrated thermoluminescent dosimeters were placed at 24 locations in an anthropomorphic phantom (Alderson Rando Phantom, Alderson Research Laboratories, New York, NY, USA), representing a medium sized adult. The following devices were tested: Heliodent Plus (Sirona Dental Systems, Bernsheim, Germany), Orthophos XG 5 (Sirona Dental Systems, Bernsheim, Germany) and i-CAT (Imaging Sciences International, Hatfield, PA, USA). The equivalent doses and effective doses were calculated considering the recommendations of the International Commission of Radiological Protection (ICRP) issued in 1990 and 2007. Results: Although the effective dose of the radiographic set corresponded to 17.5% (ICRP 1990) and 47.2% (ICRP 2007) of the CBCT dose, the equivalent doses of skin, bone surface and muscle obtained by the radiographic set were higher when compared to CBCT. However, in some areas, the radiation produced by the orthodontic set was higher due to the complete periapical examination. Conclusion: Considering the optimization principle of radiation protection, i-CAT tomography should be used only in specific and justified circumstances. Additionally, following the ALARA principle, single periapical radiographies covering restricted areas are more suitable than the complete periapical examination.